ПОСТМОДЕРНИОТ КОНЦЕПТ И ТЕРОРИЗМОТ (Филолошки студии, 2019)
This study emphasizes antagonism of the postmodern concept against the policy of globalization and “democratization” taking place in the world in the last decades. World policy differs from postmodern pluralism by the acceptance of global hegemony as a natural and constructive social process. It is grounded on quasi democracy, which unavoidably produces terrorism – the new evil that threatens the world. Today, as well as in the future, as a consequence of the ultimate democracy (everyone may influence the world system in the manner of Hard and Negri and their imaginary Empire) terrorism turns into policy of ruling. The Balkan within its diversities is a fertile soil for terrorism. Throughout the process of favor of marginal groups, it is included in the postmodern political game of the big powers bringing only misfortunes.